TEACHING ENGLISH GRAMMAR (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
This thesis explores various methods of teaching English grammar, shifting away from conventional techniques and toward more contextualized and communicative approaches. It investigates task-based learning, the efficacy of inductive and deductive approaches, and the incorporation of grammar into real-world language use. The study also examines how learner autonomy and technology might improve grammar acquisition.